Prospects for the use of solar energy in rural development Abstract - Berdimurat, N.; Abaev, A.A.; Satmurzaev, A.A.; Jussibaliyeva, A.K.; Nurmagambetova, A.Z. (BUKETOV BUSINESS REVIEW, 2022)
Object: The purpose of the article is to expand the scope of the use of renewable energy sources as a way for the future development of agricultural production based on the widespread use of new progressive technologies for the production and consumption of energy resources in rural areas. Research of theoretical and methodological foundations and justification of scientific and practical proposals. Methods: Abstract-logical, statistical, expert, comparative and structural methods. Results: Based on the used methods, there are farms in the regions of Kazakhstan that are far from the centralized power supply system, where mobile fuel power plants are used. Using the geographical coordinates of rural areas of the Republic of Kazakhstan and data from the NASA electronic database, we determined the total input of solar radiation. The largest input of the average value of solar radiation was recorded in rural areas of the South Kazakhstan region (4.32 kW/m2/day), and the lowest intensity of solar radiation is observed in the North Kazakhstan region (3.28 kW/m2/day). The analysis of the obtained data showed that the average value of solar radiation in rural areas of Ka-zakhstan varies significantly. Therefore, according to the intensity of solar radiation, three zones can b e distinguished: high (5 zones), medium (5 zones), and low (4 zones). The calculation of the duration of the light day in rural areas of Kazakhstan by month showed that almost half of the day is illuminated by the sun (from 7.48 to 17 hours a day), as well as regardless of the season. This guarantees the production of electricity during the day, as well as spare parts for excess electricity and its use in the dark hours of the day. Conclusions: “Subjects of the agro-industrial complex will be able to install solar panels with a battery, inverter, controller with a capacity of 2 kW in their farms on the basis of the passport of the project” creation of infrastructure for irrigation of pastures and water supply of livestock farms (wells). The use of solar pane ls for the development of rural areas has the following advantages: the return on investment will be realized; rural residents will be provided with sus-tainable electricity; the use of solar rays will not affect the safety of the environment.